Influence of Curriculum and Pedagogy on Adjustment of Form One Students to Secondary Schools: A Case of Nandi County, Kenya - Sarah, Dr. Bundotich (Journal of Education and Practice, 2020)
Purpose: The objective of study was to establish the influence of curriculum and pedagogy on adjustment of form one students to secondary schools. School transition being an education milestone is a process that may expose students to numerous challenges thus positive or negative impacts on the learning outcomes. The study adopted Piaget's Cognitive Learning Theory which suggests that the learner is an active participant in the process. Methodology: The research adopted survey research design and adapted a five-point summative Likert scale student questionnaire. Purposive and stratified random sampling methods were used to select a sample size of 375 form one students. Descriptive and inferential statistics were employed to analyze data. The descriptive were frequencies, means and standard deviation whereas inferential was Pearson Product Moment Correlation Coefficient. Finding: Data was statistically computed with the findings (r=0.763, Ï<0.05) indicating a strong positive relationship between Curriculum and Pedagogy and form one adjustment to secondary school. Conclusion: The study established that the introduction of many and new subjects using different approaches at form one level can result to academic dip especially to high achievers hence jeopardizing their future careers, employment prospects and life chances in general. Unique contribution to theory, practice and policy: The study recommends curriculum and pedagogy harmonization from primary to secondary schools by curriculum developers for smooth academic transition hence completion of basic education by learners. There is need for all stakeholders to prepare students psychosocially prior to transition to secondary school